PENEGAKAN HUKUM DALAM PEMBERANTASAN TINDAK PIDANA PERIKANAN DI ZONA EKONOMI EKSLUSIF INDONESIA (ZEEI) STUDI KASUS PUTUSAN PENGADILAN PERIKANAN NOMOR: 73/PID-SUS-PRK/2017/PN.RANAI) - Ganjil Sunarto (2020)
This research was conducted to find out and explain about the regulation of prosecution for fisheries crime in Decision Number 73 / Pid.Sus-Prk / 2017 / PN Ranai in the Indonesian legal system. And to explain about overcoming obstacles in law enforcement against fisheries crime. The theory used is will theory, law enforcement theory and punishment theory. The research method used is normative legal research, with a normative legal approach to analyze the norms of the applicable law, which are contained in statutory regulations and also in various court decisions containing decisions on illegal acts originating from the rental purchase agreement. The results of the study, that in the implementation of prosecution against fisheries crime, the regulation is based on Law Number 45 of 2009 concerning Amendments to Law Number 31 of 2004 concerning Fisheries from the occurrence of crimes and violations as stated in Article 103 of Law Number 31 of 2004 jo. Law Number 45 of 2009. Law enforcement in fisheries crime refers to the provisions of Chapter XIV of Law Number 31 of 2004 concerning Fisheries with several amendments based on Law Number 45 of 2009 carried out by carrying out investigations, prosecutions, evidence and examination at the fisheries court hearing. In conclusion, it is formulated that the regulation of prosecution against fisheries crime in the Indonesian legal system is not effective in tackling illegal fishing that occurs in the Indonesian Exclusive Economic Zone (ZEEI) because in the practice of criminalization against the provisions of fisheries crime there is still treatment. especially for foreign fisheries perpetrators that do not cause a deterrent effect. To overcome obstacles in prosecution of fisheries crime in order to improve law enforcement, it is necessary to make efforts by the Government of Indonesia to enter into bilateral agreements with other countries so that penalties can be applied which can have a deterrent effect on foreign criminals who commit illegal fishing. (illegal fishing) in the Indonesian Exclusive Economic Zone (ZEEI).